The Da'wah Method of Kiyai Haji Muhammad Rahmat Najieb in the Context of Reform - Muhammad Mufti Sulthanan Nasira (Al-Makki Publisher, 2025)
This study aims to analyze the da'wah methods of al-hikmah, mauidzhah hasanah, and al-mujaadalah used by KH. Muhammad Rahmat Najieb in the context of Islamic renewal (tajdid) at the PP Persis Mosque. The research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results show that KH. Muhammad Rahmat Najieb, as a productive scholar in